PMMA-Assisted Plasma Patterning of Graphene - Bobadilla, Alfredo D. (2018)
Microelectronic fabrication of Si typically involves high-temperature or high-energy processes. For instance, wafer fabrication, transistor fabrication, and silicidation are all above 500°C. Contrary to that tradition, we believe low-energy processes constitute a better alternative to enable the industrial application of single-molecule devices based on 2D materials. The present work addresses the postsynthesis processing of graphene at unconventional low temperature, low energy, and low pressure in the poly methyl-methacrylate- (PMMA-) assisted transfer of graphene to oxide wafer, in the electron-beam lithography with PMMA, and in the plasma patterning of graphene with a PMMA ribbon mask. During the exposure to the oxygen plasma, unprotected areas of graphene are converted to graphene oxide. The exposure time required to produce the ribbon patterns on graphene is 2 minutes. We produce graphene ribbon patterns with ∼50 nm width and integrate them into solid state and liquid gated transistor devices.